Gambaran Kepuasan Mahasiswa Terhadap Mata Kuliah Pendidikan Budaya Anti Korupsi Di Jurusan Ortotik Prostetik Poltekkes Kemenkes Jakarta I Tahun 2017 - Payung Hasibuan (Quality, 2018)
Background : Education service is intangible / service that can not be seen. One of the important factors for success or failure of students in attending lectures at educational institutions is the existence of good educational services and as expected for students.